PEMANFAATAN TUMBUHAN OBAT DI DESA MEKAR MAKMUR, KECAMATAN SEI LEPAN, KABUPATEN LANGKAT: STUDI ETNOBOTANI - Deby Abelia; Adi Bejo Suwardi (Universitas Nias Raya, 2026)
Ethnobotanical studies are very important to preserve local wisdom in the face of modernization. This study aimed to identify medicinal plant species utilized by the community of Mekar Makmur Village, Sei Lepan District, Langkat Regency. A quantitative descriptive method was employed through field surveys and interviews with 20 informants selected via snowball sampling. The results identified five medicinal plant species: noni (Morinda citrifolia L.) for diabetes, areca nut (Areca catechu L.) for cancer prevention, turmeric (Curcuma domestica Val.) for digestive disorders, coconut (Cocos nucifera L.) for internal heat, and soursop (Annona muricata L.) for malaria. Plant processing was carried out traditionally using fruits and leaves. The highest Use Value (UV) belonged to coconut and soursop (0.93), while noni had the lowest (0.20). These medicinal plants remain trusted and affordable treatment alternatives for the local community.